What is the heliopause? Importance of magnetic reconnection and measurement requirements - Lavraud, B.; Opher, M.; Dialynas, K.; Turner, D. L.; Eriksson, S.; Provornikova, E.; Kornbleuth, M. Z.; Mostafavi, P.; Fedorov, A.; Richardson, J. D.; Fuselier, S. A.; Drake, J.; et al. (Frontiers in Astronomy and Space Sciences, 2023)
We highlight the importance of magnetic reconnection at the Heliopause (HP), both as one of the key processes driving the interaction between solar and interstellar media, but also as an element of the definition of the HP itself. We highlight the main observations that have fed the current debates on the nature, location and shape of the HP. We explain that discriminating between the current interpretations of plasma and magnetic field structures near the HP necessitates appropriate measurements which are lacking on V1 and V2, and describe some of the ensuing requirements for thermal plasma measurements on a future Interstellar Probe. The content of this article is also accessible from the Bulletin of the American Astronomical Society (BAAS) in the framework of the Decadal Survey for Solar and Space Physics (Heliophysics) 2024-2033 (Lavraud et al., 2022).